Discovery of water-soluble semicarbazide-containing sulfonamide derivatives possessing favorable anti-glaucoma effect in vivo and drug-like properties - Yingxia Xie; Xiaoyi Wang; Hao Jia; Naying Chu (Elsevier, 2024)
In order to obtain topical and non-irritating anti-glaucoma drugs, novel semicarbazide-containing sulfonamide derivatives were designed and synthetized by sugar tail method in this study. The hydrophilic monosaccharides were expected to form interaction with the hydrophilic site of hCA II meanwhile the linker semicarbazides are used to further enhance water solubility, and more importantly, regulate the pH values of the target compounds in aqueous solution. First, all target compounds were synthesized and evaluated for their CA inhibitory activities. The results showed our target compounds demonstrated comparable activity to the positive control drug acetazolamide. The best derivative 11d exhibits an IC50 value of 14 nM for hCA II and 2086-fold selectivity over CA I. Subsequently, physicochemical properties study showed that the target compounds displayed very good water solubility (up to 3 %) and neutral pH value in solutions. Meanwhile, the artificial membrane permeability assay was performed to verify that the target compound could also pass through the membrane structure despite their strong water solubility. In the glaucomatous rabbit eye model, the applied topically representative compounds showed strongly lowered intraocular pressure (IOP), as 1 % or 2 % water solutions. Subsequent drug-like evaluation showed our target compounds possessed low hemolysis effect and low cytotoxicity toward human corneal epithelial cell line. Also, it was not found that these target compounds had significant inhibition of hERG and CYP. In addition, these novel analogs also displayed good liver microsomal metabolic stability and plasma stability. Finally, docking studies provided the rational binding modes of representative compounds in complex with hCA II. Taken together, these results suggested that compound 11d may be a promising hCA II inhibitor deserving further development.